Prevention of Occupational Diseases in Turkey: Deriving Lessons From Journey of Surveillance - Seyhan Şen; Gülşen Barlas; Selçuk Yakıştıran; İlknur G. Derin; Berna A. Şerifi; Ahmet Özlü; Lutgart Braeckman; Gert van der Laan; Frank van Dijk (Safety and Health at Work, 2019)
Introduction: To prevent and manage the societal and economic burden of occupational diseases (ODs), countries should develop strong prevention policies, health surveillance and registry systems. This study aims to contribute to the improvement of OD surveillance at national level as well as to identify priority actions in Turkey. Methods: The history and current status of occupational health studies were considered from the perspective of OD surveillance. Interpretative research was done through literature review on occupational health at national, regional and international level. Analyses were focused on countries’ experiences in policy development and practice, roles and responsibilities of institutions, multidisciplinary and intersectoral collaboration. OD surveillance models of Turkey, Belgium and the Netherlands were examined through exchange visits. Face-to-face interviews were conducted to explore the peculiarities of legislative and institutional structures, the best and worst practices, and approach principles. Results: Some countries are more focused on exploring OD trends through effective and cost-efficient researches, with particular attention to new and emerging ODs. Other countries try to reach every single case of OD for compensation and rehabilitation. Each practice has advantages and shortcomings, but they are not mutually exclusive, and thus an effective combination is possible. Conclusion: Effective surveillance and registry approaches play a key role in the prevention of ODs. A well-designed system enables monitoring and assessment of OD prevalence and trends, and adoption of preventive measures while improving the effectiveness of redressing and compensation. A robust surveillance does not only provide protection of workers’ health but also advances prevention of economic losses. Keywords: Intersectoral collaboration, Occupational diseases, Occupational health, Prevention, Worker’s health surveillance